Protein and amino acids in swine rations - Jensen, A.H.; Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
The value of a feed protein is determined by its content of available essential amino acids. For example, in relation to the pigs’ needs, corn and milo proteins are definitely deficient in the amino acid lysine. Selection of a supplemental protein, therefore, should be based on its lysine content to balance the deficiency. Experimentally, low-protein rations have been supplemented with appropriate amino acids to produce gains and efficiencies equal to those obtained on rations containing 2 to 6% more protein. Four experiments were conducted to determine the value of amino acid supplementation to mil and wheat diets and the replacement value of wheat mill feed for milo in rations for growing-finishing swine. One experiment was designed to evaluate the replacement value of milo for corn in a starter ration.
Keywords: Swine; Protein; Amino acid; Milo; Wheat